Evaluasi Pembelajaran Nahwu dalam Bentuk Munaqasyah di PP Al-Luqmaniyyah Yogyakarta - Chaqoqo, Sri Guno Najib (IAIN Salatiga, 2017)
This study discusses the evaluation model of nahwu learning in munaqasyah form at Islamic Boarding School/Pondok Pesantren (PP) Al-Luqmaniyyah Yogyakarta. The analysis is based on the theoretical framework of nahwu learning evaluation conducted at formal school and Islamic school (madrasah). With a realistic analysis to the theoretical frameworks and real conditions, the evaluation models can be mapped out; the relevance and urgency of the model in the whole lesson at this Islamic Boarding School can be known. The study results show that the munaqasyah is only applied in Alfiyah Class because this book is considered as the highest level of nahwu subject at PP Al-Luqmaniyyah. The implementation of munaqasyah to Alfiyah ibn Malik is done to measure achievement of the students (santri) in Alfiyah subject. The participation in Alfiyah continued until munaqasyah is considered as a standard that the students have followed the process gradually and completely.